The Cambridge companion to early modern women's writing - Knoppers, Laura Lunger (New York : Cambridge University Press, 2009)
"Featuring the most frequently taught female writers and texts of the early modern period, this Companion introduces the reader to the range, complexity, historical importance, and aesthetic merit of women's writing in Britain from 1500-1700. Presenting key textual, historical, and methodological information, the volume exemplifies new and diverse approaches to the study of women's writing. The book is clearly divided into three sections, covering: how women learnt to write and how their work was circulated or published; how and what women wrote in the places and spaces in which they lived, worked, and worshipped; and the different kinds of writing women produced, from poetry and fiction to letters, diaries, and political prose. This structure makes the volume readily adaptable to course usage. The Companion is enhanced by an introduction that lays out crucial framework and critical issues, and by chronologies that situate women's writings alongside political and cultural events"--Provided by publisher.
Introduction: critical framework and issues / Laura Lunger Knoppers; Part I. Material Matters: 1. Women's handwriting / Heather Wolfe; 2. Reading women / Edith Snook; 3. Manuscript miscellanies / Victoria E. Burke; 4. Women, the material book, and early printing / Marcy L. North; Part II. Sites of Production: 5. Women in educational spaces / Caroline Bowden; 6. Women in the household / Wendy Wall; 7. Women in church and in devotional spaces / Elizabeth Clarke; 8. Women in the royal courts / Karen Britland; 9. Women in the law courts / Frances E. Dolan; 10. Women in healing spaces / Mary E. Fissell; Part III. Genres and Modes: 11. Translation / Danielle Clarke; 12. Letters / James Daybell; 13. Autobiography / Ramona Wray; 14. Lyric poetry / Helen Wilcox; 15. Narrative poetry / Susanne Woods; 16. Prophecy and religious polemic / Hilary Hinds; 17. Private drama / Marta Straznicky; 18. Public drama / Derek Hughes; 19. Prose fiction / Lori Humphrey Newcomb.
Keywords: English literature -- Early modern, 1500-1700 -- History and criticism; English literature -- Women authors -- History and criticism; English literature -- Women authors; Women and literature -- Great Britain -- History -- 16th century; Women and literature -- Great Britain -- History -- 17th century